Occurrence and Flow Behavior for Oil Transport in Mixed Wetting Nanoscale Shale Bedding Fractures - Wang, Yuhan; Lei, Zhengdong; Xu, Zhenhua; Liu, Yishan; Zhou, Qiang; Liu, Pengcheng (Langmuir, 2024)
Shale reservoirs are characterized by an abundance of nanoscale porosities and microfractures. The states of fluid occurrence and flow behaviors within nanoconfined spaces necessitate novel research approaches, as traditional percolation mathematical models are inadequate for accurately depicting these phenomena. This study takes the Gulong shale reservoir in China as the subject of its research. Initially, the unique mixed wetting characteristics of the Gulong shale reservoir are examined and characterized using actual micropore images. Subsequently, the occurrence and flow behavior of oil within the nanoscale bedding fractures under various wettability scenarios are described through a combination of microscopic pore image and molecular dynamics simulations. Ultimately, a mathematical model is established that depicts the velocity distribution of oil and its apparent permeability. This study findings indicate that when the scale of the shale bedding fractures is less than 100 nm, the impact of the nanoconfinement effect is significant and cannot be overlooked. In this scenario, the state of oil occurrence and its flow behavior are influenced by the initial oil-wet surface area on the mixed wetting walls. The study quantifies the velocity and density distribution of oil in mixed wetting nanoscale shale bedding fractures through a mathematical model, providing a crucial theoretical basis for upscaling from the nanoscale to the macroscale.